Letter from Lucile Hawks to Janet Hethorn - Hawks, Lucile, author (Colorado State University. Libraries, 1987)
Letter from Lucile Hawks to Janet Hethorn regarding the history of her textile collection from Guatemala.
Keywords: Fashion -- History; Fashion -- Exhibitions